Vignettes on the World Capital Market - Harberger, Arnold C. (American Economic Review, 2016)
This paper is motivated by a sense that we as a profession need to understand, much better than we now do, how the world capital market works. We seem to be genuinely schizophrenic in the ways we build models-many of them are closedeconomy models in which the rest of the world does not even appear, yet others of them are models of the small, open economy in which hardly any degree of freedom is left for economic policy to influence events. Lying behind the schizophrenia is, I believe, a genuine ignorance on our collective part of how the world capital market